PELATIHAN MEDIA PEMBELAJARAN ANIMASI HURUF DAN ANGKA MENGGUNAKAN MICROSOFT POWER POINT DAN KINEMASTER SEBAGAI SOLUSI PJJ PADA GURU TK DI KABUPATEN NGAWI - Nur Dwi Sukmono; Pitriani Pitriani; Dhevi Agustinawati (LP4MK STKIP PGRI Lubuklinggau, 2021)
During Distance Learning, the teacher's time to be able to meet students is very limited, so the solution for this is to create learning media. Of course the learning media must be in the form of multimedia (audio-visual) so that parents can use it to do learning with their children. The purpose of this Community Service is to create animated letters and numbers using Microsoft Power Point and Kinemaster. Training aimed at early childhood educators. Target outcomes expected kindergarten educators are able to make a simple animated video to learn to recognize letters and numbers. The number of participants in this training was 63 kindergarten teachers who were conducted online in Ngawi District, Ngawi Regency. This Community Service Program includes training to make animated letters and numbers using power points. Activities carried out during the two days of the December 4 and January 7, 2021. The result of this Community Service is that they can make animated videos of letters and numbers and develop them into learning media. The average number of mastery of the practice of making animated videos of letters and numbers reached 93.4 percent. Qualitatively, the participants were able to make animated videos very well.